PEMBENTUKAN DAN PELATIHAN KADER KESEHATAN JIWA DI KELURAHAN SEPINGGAN BALIKPAPAN - Shoufiah, Rahmawati; Sipasulta, Grace Carol; Andraini, Rus (LP2M STP Mataram, 2024)
Handling problem health soul need involvement various party . This is because the cause health problems soul happen multicausal . Mental health problems caused by many interacting factors​ One each other, including factor biological , understanding and lack of religious belief , coping No constructive , psychosocial stressors , and experiences traumatic 5. The problems faced are still related high recurrence rate ODGJ sufferers in the sub-district A plate Balikpapan, namely totaling 53 people with number of 30 (56.6%) people who often experience relapse , still low number coverage service health soul in the village A piece of Balikpapan, namely by 37.35% , and not yet existence cadre health soul in the village Sepinggan Balikpapan. The purpose of activity devotion public This is the formation of mental health cadres and the decline number relapse patient disturbance soul as well as increasing the number of mental health service coverage in Sepinggan Subdistrict, Work Area Health Center A plate Balikpapan. Activity devotion public This done from June to September​​ 2024 in the Village Sepinggan Balikpapan. Activity method This is formation and training cadre health soul in frame improvement role and the Community, and the provision of education and training For increase resilience partner ward through empowerment group public sub-district and cadres as companion in community in the sub-district with give socialization about role family in nurse member the suffering family disturbance soul . The result of activity devotion public This among others Improvement knowledge cadre about health program soul with mean value of knowledge participant during the pretest was 62.8 and posttest is 78 with an increasing average knowledge of 15.2, besides That based on results evaluation in September 2024 occurs improvement coverage health soul in the village A piece of work area Health Center A plate Balikpapan from 37.35% to 39.15%, where family patient with disturbance soul Already start active For carry out control and take medicine at the Health Center